The effect of different feeding methods on the growth of melon varieties - Nizomov Rustam; Sadullayev Sanjarbek; Yusupova Azada; Axmedov Ilxom O’g’li Rustamboy; Sabirova Kudrat Qizi Munisaxon (BIO Web of Conferences)
Experimental cultivation of medium-sized varieties of melon with strong growth of the aboveground part by adding a gidrogel substance to the soil and achieving high results.It should be noted that in the experiment, the effect of various soil mixtures and standards on the yield index was determined in the cultivation of medium-ripe varieties of melon. In the experiment was determined, that the yield level was 108.9-132.0% in the Kokcha variety, 102.2-136.8% in the Gurvak variety, and 200.2-210.1% in the Qari-qiz variety and the profitability of all varieties was strongly affected in the variant with the background and gidrogel substance applied at 12 kg/ha, and a high result was observed.The best result were 13% in the varieties of Kokcha (20.2 t/ha), 21% in Gurvak (20.8 t/ha) and Qari-qiz variety (30.3 t/ha). ga) It was found that 9 percent higher yield was obtained than the control option. Use of sedating substances in the planting of melon seeds in the conditions of Khorezm region.